Microbial Degradation of Lignocellulose: the Lignin Component - Crawford, Don L. (1976)
A new procedure was developed for the study of lignin biodegradation by pure or mixed cultures of microorganisms. Natural lignocelluloses were prepared containing (14)C in primarily their lignin components by feeding plants l-[U-(14)C]phenylalanine through their cut stems. Lignin degradation was observed in numerous soils by monitoring evolution of (14)CO(2) from [(14)C]lignin-labeled oak (Quercus albus), maple (Acer rubrum), and cattail (Typha latifola). An organism (Thermonospora fusca ATCC 27730) that is known to degrade cellulose but not lignin was shown to grow on lignocellulose in the presence of [(14)C]lignocelluloses without evolution of (14)CO(2). A known lignin degrader (a white-rot fungus, Polyporus versicolor) was shown to readily evolve (14)CO(2) from damp (14)C-labeled cattail and (14)C-labeled maple.